Composition of ferulic acid and chitosan and its application

Through the combination technology of ferulic acid and chitosan, the problems of solubility and stability of ferulic acid in aqueous systems are solved, and its effective application and antioxidant effects in water-based cosmetics are achieved.

CN119770376APending Publication Date: 2025-04-08SHANGHAI JAHWA UNITED
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311289714.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-07
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Ferulic acid is limited in its application in cosmetics due to its low solubility and oxidative inactivation, especially in aqueous systems, which are difficult to dissolve and maintain stability.

Method used

By combining ferulic acid with chitosan in a certain proportion, the obtained compound composition is easily soluble in aqueous matrix, while improving the stability of ferulic acid.

Benefits of technology

It has achieved the effective application of ferulic acid in water-based cosmetics, and has the effects of antioxidant, delaying aging, brightening, removing fine wrinkles and resisting sunlight.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119770376A_ABST
    Figure CN119770376A_ABST
Patent Text Reader

Abstract

The present invention provides a composition comprising chitosan and ferulic acid, wherein the weight ratio of chitosan to ferulic acid is 0.7-0.8:1, and the pH of the composition is 4-7. The present invention also relates to a preparation method of the composition comprising chitosan and ferulic acid and application of the composition in cosmetics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of polymer chemistry and cosmetics, and in particular to a composite composition of ferulic acid and chitosan, and a preparation method and application thereof. Background Art

[0002] Ferulic acid, chemically known as 3-methoxy-4-hydroxycinnamic acid, is a chemical naturally found in many plants. It is found in high concentrations in traditional Chinese medicines such as asafoetida, angelica sinensis, chuanxiong, cimicifuga, and jujube seeds, and is one of the active ingredients of these traditional Chinese medicines. Ferulic acid has two isomers, cis and trans, both of which are pale yellow solids. Ferulic acid is a free radical scavenger, which means it can find harmful free radicals and neutralize them. Free radicals are molecules that attack and damage cells in our bodies. In our skin, free radical damage can cause wrinkles and other signs of aging, and can also make the skin more susceptible to cancer. Antioxidants such as ferulic acid can block the damaging effects of free radicals. It prevents cell damage, thereby slowing down the visible aging process. It also provides some protection against carcinogenic ultraviolet damage to skin cells. However, due to its limited solubility and its easy oxidative inactivation, ferulic acid has great technical barriers to its use in cosmetics.

[0003] Chitosan, also known as chitosan, is a white or off-white powder obtained by deacetylation of chitin, which is widely found in nature. Its chemical name is polyglucosamine (1-4)-2-amino-BD glucose. It has the functions of moisturizing, wound repairing, sterilizing and auxiliary preservation. However, it must be neutralized with dilute acid before it can be dissolved in water, so it is difficult to use directly.

[0004] For example, Chinese patent CN105581919 discloses a ferulic acid phospholipid complex and its use in preparing cosmetics with whitening effect. The ferulic acid phospholipid complex of the present invention is obtained by heating and stirring ferulic acid and phospholipid in a non-protonic solvent, and removing the non-protonic solvent. The present invention also provides a cosmetic with whitening effect containing a ferulic acid phospholipid complex, including skin care oil, lotion and cream with whitening effect. The present invention changes the physicochemical properties of ferulic acid by compounding ferulic acid and phospholipid, enhances its fat solubility, stability and water dispersibility, improves its transmembrane transport performance, and thus improves its bioavailability. 30 female volunteers aged 25 to 45 years used the whitening skin care lotion containing the ferulic acid phospholipid complex for 30 days, and the facial melanin content was significantly reduced, the skin brightness was increased, and the skin MI value, L* value and ITA° value were significantly different from the initial value (P<0.05), indicating that the whitening lotion has a good whitening effect on the human body.

[0005] For example, Chinese patent CN101485447 relates to ferulic acid cyclodextrin or cyclodextrin derivative inclusion compound and preparation method thereof. Ferulic acid has the effects of anti-inflammatory, analgesic, anti-thrombotic, anti-tumor, anti-ultraviolet radiation, anti-free radical, and regulating human immune function, regulating endocrine, improving microcirculation and anti-fatigue, but ferulic acid itself is insoluble in water, unstable in nature, and sensitive to light and heat, which greatly limits its application in food and medicine. The present invention uses cyclodextrin and cyclodextrin derivatives to include ferulic acid to prepare ferulic acid cyclodextrin or cyclodextrin derivative inclusion compound, solves the problems of low water solubility and poor stability of ferulic acid, and enables ferulic acid to be directly applied to food, medicine and health products.

[0006] Different from the above-mentioned technologies, the present invention first discovered that ferulic acid can be compounded with chitosan, so that ferulic acid can be used in an aqueous system while improving the stability of ferulic acid. The compound composition prepared by the present invention can be conveniently applied to water-based cosmetics to exert the effects of anti-oxidation, anti-aging, brightening, removing fine wrinkles and resisting sun exposure. Summary of the invention

[0007] In one aspect, a composition comprising chitosan and ferulic acid is provided, wherein the weight ratio of chitosan to ferulic acid is 0.7-0.8:1, and the pH of the composition is 2-7.

[0008] In a preferred embodiment, the composition of the present invention further comprises ethanol or a polyol, wherein the polyol is selected from propylene glycol, butylene glycol, glycerol, hexylene glycol, or a combination thereof.

[0009] In a preferred embodiment, the content of ferulic acid in the composition of the present invention is 0.1-3% by weight, the content of chitosan is 0.1-3% by weight. In a preferred embodiment, the amount of ethanol or polyol is 5-30% by weight.

[0010] In another aspect, the present invention provides a method for preparing a composition comprising chitosan and ferulic acid, the method comprising the following steps:

[0011] a) dissolving chitosan with ethanol or polyol;

[0012] b) adding chitosan according to the weight ratio of chitosan to ferulic acid of 0.7-0.8:1, stirring until dissolved,

[0013] c) adding water to obtain a composition comprising chitosan and ferulic acid.

[0014] In another aspect, the present invention also relates to the use of a composition comprising chitosan and ferulic acid in cosmetics. In a preferred embodiment, the cosmetics are water-based cosmetics, and the cosmetics further comprise excipients acceptable in the cosmetics field. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The photos of chitosan, ferulic acid and the samples obtained by mixing the two are shown. From left to right, they are 0.8% chitosan-15% ethanol aqueous solution, 1% ferulic acid-15% ethanol aqueous solution, and 0.8% chitosan-1% ferulic acid-15% ethanol aqueous solution. DETAILED DESCRIPTION

[0016] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as commonly understood by those of ordinary skill in the art to which the invention belongs. Although any methods and materials similar or equivalent to those described herein can be used to implement or test the present invention, preferred methods and materials are described herein. For purposes of the present invention, the following terms are defined below.

[0017] In order to provide a more concise description, some quantitative expressions given herein are not modified by the term "about". It should be understood that, whether or not the term "about" is explicitly used, each quantity given herein is intended to refer to the actual given value, and is also intended to refer to the approximate values ​​of these given values ​​that can be reasonably inferred by ordinary technicians in the field, including the approximate values ​​of these given values ​​caused by experimental and / or measurement conditions.

[0018] To provide a more concise description, some quantitative expressions herein are described as a range of about X amount to about Y amount. It should be understood that when describing a range, the range is not limited to the upper and lower limits described, but should include the entire range of about X amount to about Y amount or any amount therebetween.

[0019] The object of the present invention is to provide a composite composition of ferulic acid and deacetylated chitosan for skin care. The composition prepared according to the provided formula and preparation method can be conveniently applied to water-based cosmetics while ensuring the active content of ferulic acid.

[0020] The present invention is based on the following unexpected discovery: when ferulic acid and chitosan are compounded in a certain ratio, the obtained composition is easily soluble in an aqueous matrix, and the stability of ferulic acid is improved. Therefore, the compound composition prepared by the present invention can be conveniently applied to water-based cosmetics to exert the effects of anti-oxidation, anti-aging, brightening, removing fine wrinkles and resisting sun exposure.

[0021] Ferulic acid

[0022] Ferulic acid is a free radical scavenger, which means it finds harmful free radicals and neutralizes them. Free radicals are molecules that attack and damage cells in our bodies. In our skin, free radical damage causes wrinkles and other signs of aging, and can also make the skin more susceptible to cancer. Ferulic acid acts as an antioxidant to block the damaging effects of free radicals. It prevents cell damage, thereby slowing the visible aging process. It also provides some protection against carcinogenic UV damage to skin cells. However, ferulic acid has a large technical barrier to use in cosmetics due to its limited solubility and its susceptibility to oxidative inactivation.

[0023] The composition of the present invention comprises ferulic acid, and can realize a water-based product comprising ferulic acid while maintaining the stability of ferulic acid. In a specific embodiment, the composition of the present invention uses ferulic acid purchased from Aoli Oil Press Co., Ltd.

[0024] In some embodiments, the composition of the present invention comprises 0.1-3 wt% ferulic acid. In a preferred embodiment, the composition of the present invention comprises 0.1-2 wt%, more preferably 1 wt% ferulic acid.

[0025] Chitosan

[0026] Chitosan, also known as chitosan, has the functions of moisturizing, wound repairing, sterilizing and auxiliary antiseptic. However, it must be neutralized with dilute acid before it can be dissolved in water, and it is difficult to use directly.

[0027] The present invention firstly finds that ferulic acid can be compounded with chitosan, so that the compounded composition can be used in an aqueous system while maintaining the stability of ferulic acid. In a specific embodiment, the composition of the present invention uses chitosan purchased from Shanghai Enfei Chemicals Co., Ltd.

[0028] In some embodiments, the composition of the present invention comprises 0.1-3 wt% chitosan. In a preferred embodiment, the composition of the present invention comprises 0.5-3 wt%, more preferably 0.7-0.9 wt% chitosan.

[0029] Composition of ferulic acid and chitosan

[0030] The composition of the present invention comprises chitosan and ferulic acid, wherein the weight ratio of chitosan to ferulic acid is 0.7-0.8:1.

[0031] In some embodiments, the composition of the present invention further comprises a polyol. In a preferred embodiment, the polyol is selected from: ethanol, propylene glycol, butylene glycol, glycerol, hexylene glycol, or a combination thereof. In a preferred embodiment, the polyol is ethanol.

[0032] In some embodiments, the composition of the present invention comprises 5-30 wt% polyol. In a preferred embodiment, the composition of the present invention comprises 10-30 wt%, more preferably 12-30 wt% polyol.

[0033] The composition of the present invention can be used in an aqueous system, such as an aqueous system having a water content of at least 20 wt%. In some embodiments, the water content of the aqueous system is at least 30 wt%, at least 40 wt%, at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 75 wt%. In a preferred embodiment, the water content of the aqueous system is 20-85 wt%, preferably 30-85 wt%, 40-85 wt%, 50-85 wt%, 60-85 wt%, 70-85 wt%, 75-85 wt%.

[0034] In some embodiments, the compositions of the present invention comprise the following ingredients:

[0035] 0.1-3 parts by weight of chitosan;

[0036] 0.1-3 parts by weight of ferulic acid;

[0037] 5-30 parts by weight of a polyol; and

[0038] 1-80 parts by weight of water.

[0039] In a preferred embodiment, the composition of the present invention comprises the following ingredients:

[0040] 0.5-3 parts by weight of chitosan;

[0041] 0.1-2 parts by weight of ferulic acid;

[0042] 10-30 parts by weight of a polyol; and

[0043] 20-80 parts by weight of water.

[0044] In a preferred embodiment, the pH of the composition of the present invention is 2.0-7.0. In some preferred embodiments, the pH of the composition of the present invention is 4.0-7.0.

[0045] The present invention is further described below in conjunction with specific examples. It is necessary to point out that the examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of the present invention. Those skilled in the art can make some non-essential improvements and adjustments based on the content of the present invention described above. The test methods in the following examples that do not specify specific conditions are usually based on conventional conditions or the conditions recommended by the manufacturer. Unless otherwise stated, all percentages and parts are by weight.

[0046] The experimental materials used in the embodiments of the present invention are as follows:

[0047] Ethanol, trade name edible alcohol (special grade), was purchased from Anhui Ante Food Co., Ltd.;

[0048] Glycerin, trade name Baomei Le G995U, purchased from Tyco Palm Chemical (Zhangjiagang) Co., Ltd.;

[0049] Propylene glycol, trade name Propanediol, purchased from Primient Covation LLC;

[0050] Butanediol, trade name 1,3-Butylene Glycol, purchased from DAICEL CORPORATION;

[0051] Hexanediol, trade name SHD62, purchased from SHINSUNG MATERIAL CO., LTD.;

[0052] Chitosan, trade name CRECARE MPG-L, was purchased from Shanghai Enfei Chemicals Co., Ltd.;

[0053] Ferulic acid, trade name ORYZAFERULIX, purchased from ORYZA Chemical Co., Ltd.

[0054] Vitamin A palmitate, trade name Vitamin A Palmitate 1.7 MIU / g, purchased from DSM Nutritional Products Ltd.;

[0055] Vitamin E, trade name DL-alpha-Tocopherol, purchased from DSM Nutritional Products Ltd.;

[0056] Resveratrol, trade name Resveratrol, was purchased from Dongming Grus Biotechnology Co., Ltd.

[0057] Example 1: Preparation of a composite composition of ferulic acid and chitosan

[0058] Weigh 1 part by mass of ferulic acid and 15 parts by mass of ethanol, mix and dissolve, add 0.5 parts by mass of chitosan, mix and stir at room temperature at a speed of 100 rpm until all dissolved; add deionized water to make up to 100, continue to mix and stir at a speed of 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0059] Example 2: Preparation of a composite composition of ferulic acid and chitosan

[0060] Weigh 1 part by mass of ferulic acid and 15 parts by mass of ethanol, mix and dissolve, add 0.8 parts by mass of chitosan, mix and stir at room temperature at a speed of 100 rpm until all dissolved; add deionized water to make up to 100, continue to mix and stir at a speed of 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0061] Example 3: Preparation of a composite composition of ferulic acid and chitosan

[0062] Weigh 1 part by mass of ferulic acid and 15 parts by mass of ethanol, mix and dissolve, add 1 part by mass of chitosan, mix and stir at room temperature at a speed of 100 rpm until all dissolved; add deionized water to make up to 100, continue to mix and stir at a speed of 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0063] Example 4: Preparation of a composite composition of ferulic acid and chitosan

[0064] Weigh 1 part by mass of ferulic acid and 15 parts by mass of ethanol, mix and dissolve, add 1.2 parts by mass of chitosan, mix and stir at room temperature at a speed of 100 rpm until all dissolved; add deionized water to make up to 100, continue to mix and stir at a speed of 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0065] Example 5: Preparation of a composite composition of ferulic acid and chitosan

[0066] Weigh 1 part by mass of ferulic acid and 15 parts by mass of ethanol, mix and dissolve, add 0.7 parts by mass of chitosan, mix and stir at room temperature at a speed of 100 rpm until all dissolved; add deionized water to make up to 100, continue to mix and stir at a speed of 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0067] Example 6: Preparation of Ferulic Acid Composition

[0068] Weigh 1 part by mass of ferulic acid and 15 parts by mass of ethanol, mix and dissolve, stir at room temperature at 100 rpm until all dissolved; add deionized water to make up to 100, continue to stir at 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0069] Test Example 1: Ferulic acid content and stability test

[0070] After measuring the ferulic acid content of Examples 1-6, the stability thereof was investigated.

[0071] Detection method of ferulic acid content: high performance liquid chromatography (with ultraviolet detector), high performance liquid chromatography conditions: chromatographic column: Agilent ZORBAX SB-C18 chromatographic column (250mm×4.6mm, 5m); mobile phase: phase A: acetonitrile; phase B: 1% acetic acid solution; A:B=35:65; flow rate: 1.0ml / min; detection wavelength: 311nm; column temperature: 25°C; accurately weigh 0.10g (accurate to 0.0001g) of ferulic acid reference substance in a 100ml volumetric flask, dissolve the mobile phase, ultrasonically oscillate until completely clear, and dilute to the scale. Then transfer 0.10, 0.50, 1.00, 1.50, and 2.00 ml of the test solution to a 10 ml volumetric flask, dissolve it to the mark with mobile phase, shake well, and form a standard sample series with concentrations of 0.01, 0.05, 0.10, 0.15, and 0.20 mg / ml.

[0072] Product sample solution: weigh 0.50g of product sample (accurate to 0.0001g) in a 50ml stoppered colorimetric tube, 0.1g of raw material sample, add mobile phase to dissolve, oscillate and disperse evenly, ultrasonically extract for 15min, cool to room temperature, dilute to scale with mobile phase, vortex and shake well, then filter through a 0.45um organic filter membrane for use. The filtrate can be diluted with mobile phase solution as needed. Accurately measure 10uL of standard sample solution and sample solution to be tested, inject into liquid chromatograph, record the peak area of ​​reference solution and sample solution, and then calculate.

[0073] The stability evaluation method is as follows: the liquid composition prepared in Examples 1-6 is placed in a thermostat at a high temperature (48°C, 25°C, 4°C) and observed for 30 days. Observe whether the sample has solid precipitation of particles, jelly of the material, stratification, etc. If the sample is normal and unchanged before and after a certain time within 30 days, it means "passed", the appearance of particles means "precipitation", the phenomenon that the material solidifies and is difficult to flow means "jelly", and the phenomenon of two layers of liquid above and below means "stratification". The results are shown in the following table.

[0074] Table 1: Stability study of different raw materials

[0075]

[0076] Conclusion: The composite compositions of ferulic acid and chitosan in different proportions were prepared, and the optimal composite ratio of chitosan and ferulic acid was investigated, and the stabilizing effect on the ferulic acid content and the stability of the composite composition were investigated. The optimal composite ratio of chitosan and ferulic acid ranged from 0.7:1 to 0.8:1. According to the ferulic acid content and stability results in the above table, Examples 2 and 5 can produce composite compositions with the highest ferulic acid content and stable systems, and the aqueous solution in the composite composition can contain more than 97% ferulic acid.

[0077] Test Example 2: Product appearance and turbidity test

[0078] Test sample: Composition prepared in Examples 1-6

[0079] Product appearance evaluation: A five-person evaluation panel evaluates the product appearance (transparency) by observing and trying the product, and then scores and takes the average of the five-person evaluation panel, 0-10 points: 0 points is poor; 10 points is excellent.

[0080] Turbidity test: Use SZD-1 scattered light tabletop turbidity meter, test the sample six times after zero calibration, and take the average value as the turbidity value. The greater the turbidity, the lower the transparency. >1000NTU means that it exceeds the measurement range of the instrument or the detector signal is too low.

[0081] Table 2: Product appearance and turbidity test results

[0082]

[0083] Conclusion: The composite compositions of ferulic acid and chitosan in different proportions were prepared, and the optimal composite ratio of chitosan and ferulic acid was investigated to investigate the effect on the transparency of the system. The optimal composite ratio of chitosan and ferulic acid ranged from 0.7:1 to 0.8:1. According to the product appearance scoring and turbidity results in the above table, Examples 2 and 5 can produce composite compositions with the highest transparency and the best appearance.

[0084] Example 7: Preparation of a composite composition of ferulic acid and chitosan

[0085] Weigh 1 part by mass of ferulic acid and 10 parts by mass of ethanol, mix and dissolve, add 0.8 parts by mass of chitosan, mix and stir at room temperature at a speed of 100 rpm until all dissolved; add deionized water to make up to 100, continue to mix and stir at a speed of 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0086] Example 8: Preparation of a composite composition of ferulic acid and chitosan

[0087] Weigh 1 part by mass of ferulic acid and 12 parts by mass of ethanol, mix and dissolve, add 0.8 parts by mass of chitosan, mix and stir at room temperature at a speed of 100 rpm until all dissolved; add deionized water to make up to 100, continue to mix and stir at a speed of 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0088] Example 9: Preparation of a composite composition of ferulic acid and chitosan

[0089] Weigh 1 part by mass of ferulic acid and 18 parts by mass of ethanol, mix and dissolve, add 0.8 parts by mass of chitosan, mix and stir at room temperature at a speed of 100 rpm until all dissolved; add deionized water to make up to 100, continue to mix and stir at a speed of 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0090] Example 10: Preparation of a composite composition of ferulic acid and chitosan

[0091] Weigh 1 part by mass of ferulic acid and 20 parts by mass of ethanol, mix and dissolve, add 0.8 parts by mass of chitosan, mix and stir at room temperature at a speed of 100 rpm until all dissolved; add deionized water to make up to 100, continue to mix and stir at a speed of 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0092] Test Example 3: Ferulic acid content and stability test

[0093] After measuring the ferulic acid content of Examples 7-10, the stability thereof was investigated.

[0094] Detection method of ferulic acid content: high performance liquid chromatography (with ultraviolet detector), high performance liquid chromatography conditions: chromatographic column: Agilent ZORBAX SB-C18 chromatographic column (250mm×4.6mm, 5m); mobile phase: phase A: acetonitrile; phase B: 1% acetic acid solution; A:B=35:65; flow rate: 1.0ml / min; detection wavelength: 311nm; column temperature: 25°C; accurately weigh 0.10g (accurate to 0.0001g) of ferulic acid reference substance in a 100ml volumetric flask, dissolve the mobile phase, ultrasonically oscillate until completely clear, and dilute to the scale. Then transfer 0.10, 0.50, 1.00, 1.50, and 2.00 ml of the test solution to a 10 ml volumetric flask, dissolve it to the mark with mobile phase, shake well, and form a standard sample series with concentrations of 0.01, 0.05, 0.10, 0.15, and 0.20 mg / ml.

[0095] Product sample solution: weigh 0.50g of product sample (accurate to 0.0001g) in a 50ml stoppered colorimetric tube, 0.1g of raw material sample, add mobile phase to dissolve, oscillate and disperse evenly, ultrasonically extract for 15min, cool to room temperature, dilute to scale with mobile phase, vortex and shake well, then filter through a 0.45um organic filter membrane for use. The filtrate can be diluted with mobile phase solution as needed. Accurately measure 10uL of standard sample solution and sample solution to be tested, inject into liquid chromatograph, record the peak area of ​​reference solution and sample solution, and then calculate.

[0096] The stability evaluation method is as follows: the liquid composition prepared in Examples 7-10 is placed in a thermostat at a high temperature (48°C, 25°C, 4°C) and observed for 30 days. Observe whether the sample has solid precipitation of particles, jelly of the material, stratification, etc. If the sample is normal and unchanged before and after a certain time within 30 days, it means "passed", the appearance of particles means "precipitation", the phenomenon that the material solidifies and is difficult to flow means "jelly", and the phenomenon of two layers of liquid above and below means "stratification". The results are shown in the following table.

[0097] Table 3: Stability study of different raw materials

[0098]

[0099] Conclusion: A composite composition of ferulic acid and chitosan containing different proportions of ethanol was prepared, and the optimal ethanol ratio in the composite composition of ferulic acid and chitosan, and the stabilizing effect on the ferulic acid content and the stability of the composite composition were investigated. The optimal ethanol ratio range is 12%-20%. According to the ferulic acid content and stability results in the above table, Examples 8 to 10 can produce composite compositions with the highest ferulic acid content and a stable system, and the aqueous solution in the composite composition can contain a high level of ferulic acid.

[0100] Test Example 4: Product appearance and turbidity test

[0101] Test sample: Composition prepared in Examples 7-10

[0102] Product appearance evaluation: A five-person evaluation panel evaluates the product appearance (transparency) by observing and trying the product, and then scores and takes the average of the five-person evaluation panel, 0-10 points: 0 points is poor; 10 points is excellent.

[0103] Turbidity test: Use SZD-1 scattered light tabletop turbidity meter, test the sample six times after zero calibration, and take the average value as the turbidity value. The greater the turbidity, the lower the transparency. >1000NTU means that it exceeds the measurement range of the instrument or the detector signal is too low.

[0104] Table 4: Product appearance and turbidity test results

[0105]

[0106] Conclusion: A composite composition of ferulic acid and chitosan containing different proportions of ethanol was prepared, and the optimal ethanol ratio in the composite composition of ferulic acid and chitosan and the effect on the transparency of the system were investigated. The optimal ethanol ratio range is 12%-20%. According to the product appearance scoring and turbidity results in the above table, Examples 8 to 10 can produce composite compositions with the highest transparency and the best appearance.

[0107] Example 11: Preparation of a composite composition of ferulic acid and chitosan

[0108] Weigh 1 part by mass of ferulic acid and 15 parts by mass of propylene glycol, mix and dissolve, add 0.5 parts by mass of chitosan, mix and stir at room temperature at a speed of 100 rpm until all dissolved; add deionized water to make up to 100, continue to mix and stir at a speed of 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0109] Example 12: Preparation of a composite composition of ferulic acid and chitosan

[0110] Weigh 1 part by mass of ferulic acid and 15 parts by mass of butanediol, mix and dissolve, add 0.7 parts by mass of chitosan, mix and stir at room temperature at a speed of 100 rpm until all dissolved; add deionized water to make up to 100, continue to mix and stir at a speed of 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0111] Example 13: Preparation of a composite composition of ferulic acid and chitosan

[0112] Weigh 1 part by mass of ferulic acid and 15 parts by mass of glycerol, mix and dissolve, add 0.7 parts by mass of chitosan, mix and stir at room temperature at a speed of 100 rpm until all dissolved; add deionized water to make up to 100, continue to mix and stir at a speed of 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0113] Example 14: Preparation of a composite composition of ferulic acid and chitosan

[0114] Weigh 1 part by mass of ferulic acid and 15 parts by mass of hexylene glycol, mix and dissolve, add 0.7 parts by mass of chitosan, mix and stir at room temperature at a speed of 100 rpm until all dissolved; add deionized water to make up to 100, continue to mix and stir at a speed of 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0115] Example 15: Preparation of a composite composition of ferulic acid and chitosan

[0116] Weigh 1 part by mass of ferulic acid and 15 parts by mass of propylene glycol, mix and dissolve, add 0.7 parts by mass of chitosan, mix and stir at room temperature at a speed of 100 rpm until all dissolved; add deionized water to make up to 100, continue to mix and stir at a speed of 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0117] Example 16: Preparation of a composite composition of ferulic acid and chitosan

[0118] Weigh 1 part by mass of ferulic acid and 15 parts by mass of pentanediol, mix and dissolve, add 0.7 parts by mass of chitosan, mix and stir at room temperature at a speed of 100 rpm until all dissolved; add deionized water to make up to 100, continue to mix and stir at a speed of 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0119] Example 17: Preparation of a composite composition of ferulic acid and chitosan

[0120] Weigh 1 part by mass of ferulic acid and 15 parts by mass of butanediol, mix and dissolve, add 0.9 parts by mass of chitosan, mix and stir at room temperature at a speed of 100 rpm until all dissolved; add deionized water to make up to 100, continue to mix and stir at a speed of 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0121] Test Example 5: Ferulic acid content and stability test

[0122] After measuring the ferulic acid content of Examples 11-17, the stability thereof was investigated.

[0123] Detection method of ferulic acid content: high performance liquid chromatography (with ultraviolet detector), high performance liquid chromatography conditions: chromatographic column: Agilent ZORBAX SB-C18 chromatographic column (250mm×4.6mm, 5m); mobile phase: phase A: acetonitrile; phase B: 1% acetic acid solution; A:B=35:65; flow rate: 1.0ml / min; detection wavelength: 311nm; column temperature: 25°C; accurately weigh 0.10g (accurate to 0.0001g) of ferulic acid reference substance in a 100ml volumetric flask, dissolve the mobile phase, ultrasonically oscillate until completely clear, and dilute to the scale. Then transfer 0.10, 0.50, 1.00, 1.50, and 2.00 ml of the test solution to a 10 ml volumetric flask, dissolve it to the mark with mobile phase, shake well, and form a standard sample series with concentrations of 0.01, 0.05, 0.10, 0.15, and 0.20 mg / ml.

[0124] Product sample solution: weigh 0.50g of product sample (accurate to 0.0001g) in a 50ml stoppered colorimetric tube, 0.1g of raw material sample, add mobile phase to dissolve, oscillate and disperse evenly, ultrasonically extract for 15min, cool to room temperature, dilute to scale with mobile phase, vortex and shake well, then filter through a 0.45um organic filter membrane for use. The filtrate can be diluted with mobile phase solution as needed. Accurately measure 10uL of standard sample solution and sample solution to be tested, inject into liquid chromatograph, record the peak area of ​​reference solution and sample solution, and then calculate.

[0125] The stability evaluation method is as follows: the liquid compositions prepared in Examples 11-17 are placed in a thermostat at a high temperature (48°C, 25°C, 4°C) and observed for 30 days. Observe whether the samples have solid precipitation of particles, jellying of the material, stratification, etc. If the sample is normal and unchanged before and after a certain time within 30 days, it means "passed", the appearance of particles means "precipitation", the phenomenon that the material solidifies and is difficult to flow means "jelly", and the phenomenon of two layers of liquid above and below means "stratification". The results are shown in the following table.

[0126] Table 5: Stability study of different raw materials

[0127]

[0128] Conclusion: A composite composition of ferulic acid and chitosan containing different types of polyols was prepared, and the optimal polyol in the composite composition of ferulic acid and chitosan was investigated, as well as the stabilizing effect on the ferulic acid content and the influence on the stability of the composite composition. Combined with the above experiments, the most preferred polyols are ethanol, butanediol, hexanediol, and propylene glycol. According to the ferulic acid content and stability results in the above table, Examples 14 to 17 can produce composite compositions with stable systems, and the aqueous solutions in the composite compositions of Examples 14, 15, and 17 can contain relatively high levels of ferulic acid.

[0129] Test Example 6: Product appearance and turbidity test

[0130] Test sample: Compositions prepared in Examples 11-17

[0131] Product appearance evaluation: A five-person evaluation panel evaluates the product appearance (transparency) by observing and trying the product, and then scores and takes the average of the five-person evaluation panel, 0-10 points: 0 points is poor; 10 points is excellent.

[0132] Turbidity test: Use SZD-1 scattered light tabletop turbidity meter, test the sample six times after zero calibration, and take the average value as the turbidity value. The greater the turbidity, the lower the transparency. >1000NTU means that it exceeds the measurement range of the instrument or the detector signal is too low.

[0133] Table 6: Product appearance and turbidity test results

[0134]

[0135] Conclusion: A composite composition of ferulic acid and chitosan containing different types of polyols was prepared, and the optimal polyol in the composite composition of ferulic acid and chitosan was investigated, as well as the effect on the transparency of the system. Combined with the above experiments, the most preferred polyols are ethanol, butanediol, hexanediol, and propylene glycol. According to the product appearance scores and turbidity results in the above table, Examples 14 to 17 can produce composite compositions with the highest transparency and the best appearance.

[0136] Example 18: Preparation of a composite composition of resveratrol and chitosan

[0137] Weigh 1 part by mass of resveratrol and 15 parts by mass of ethanol, mix and dissolve, add 0.7 parts by mass of chitosan, mix and stir at room temperature at a speed of 100 rpm until all dissolved; add deionized water to make up to 100, continue to mix and stir at a speed of 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0138] Example 19: Preparation of a composite composition of vitamin E and chitosan

[0139] Weigh 1 part by mass of vitamin E and 15 parts by mass of ethanol, mix and dissolve, add 0.7 parts by mass of chitosan, mix and stir at room temperature at a speed of 100 rpm until all dissolved; add deionized water to make up to 100, continue to mix and stir at a speed of 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0140] Example 20: Preparation of a composite composition of vitamin A palmitate and chitosan

[0141] Weigh 1 part by mass of vitamin A palmitate and 15 parts by mass of ethanol, mix and dissolve, add 0.7 parts by mass of chitosan, mix and stir at room temperature at a speed of 100 rpm until all dissolved; add deionized water to make up to 100, continue to mix and stir at a speed of 100 rpm for 20-30 minutes, then stand at room temperature for 12 hours for use.

[0142] Test Example 7: Active agent content and stability test

[0143] After measuring the active agent content of Examples 18-20, the stability thereof was investigated.

[0144] Detection method of active agent content: high performance liquid chromatography (with ultraviolet detector), high performance liquid chromatography conditions: chromatographic column: Agilent ZORBAX SB-C18 chromatographic column (250mm×4.6mm, 5m); mobile phase: phase A: acetonitrile; phase B: 1% acetic acid solution; A:B=35:65; flow rate: 1.0ml / min; detection wavelength: 311nm; column temperature: 25°C; accurately weigh 0.10g (accurate to 0.0001g) of the reference substance in a 100ml volumetric flask, dissolve the mobile phase, ultrasonically oscillate until completely clear, and dilute to the scale. Then transfer 0.10, 0.50, 1.00, 1.50, and 2.00 ml of the test solution to a 10 ml volumetric flask, dissolve it to the mark with mobile phase, shake well, and form a standard sample series with concentrations of 0.01, 0.05, 0.10, 0.15, and 0.20 mg / ml.

[0145] Product sample solution: weigh 0.50g of product sample (accurate to 0.0001g) in a 50ml stoppered colorimetric tube, 0.1g of raw material sample, add mobile phase to dissolve, oscillate and disperse evenly, ultrasonically extract for 15min, cool to room temperature, dilute to scale with mobile phase, vortex and shake well, then filter through a 0.45um organic filter membrane for use. The filtrate can be diluted with mobile phase solution as needed. Accurately measure 10uL of standard sample solution and sample solution to be tested, inject into liquid chromatograph, record the peak area of ​​reference solution and sample solution, and then calculate.

[0146] The stability evaluation method is as follows: the liquid composition prepared in Examples 18-20 is placed in a thermostat at a high temperature (48°C, 25°C, 4°C) and observed for 30 days. Observe whether the sample has solid precipitation of particles, jelly of the material, stratification, etc. If the sample is normal and unchanged before and after a certain time within 30 days, it means "passed", the appearance of particles means "precipitation", the phenomenon that the material solidifies and is difficult to flow means "jelly", and the phenomenon of two layers of liquid above and below means "stratification". The results are shown in the following table.

[0147] Table 7: Stability study of different raw materials

[0148]

[0149] Conclusion: A composite composition containing an alcohol-soluble or oil-soluble active ingredient and chitosan was prepared to investigate the composite effect of the active ingredient and chitosan. According to the active ingredient content and stability results in the above table, the composite compositions prepared in Examples 18 to 20 were all unstable.

[0150] Test Example 8: Product appearance and turbidity test

[0151] Test sample: Composition prepared in Examples 18-20

[0152] Product appearance evaluation: A five-person evaluation panel evaluates the product appearance (transparency) by observing and trying the product, and then scores and takes the average of the five-person evaluation panel, 0-10 points: 0 points is poor; 10 points is excellent.

[0153] Turbidity test: Use SZD-1 scattered light tabletop turbidity meter, test the sample six times after zero calibration, and take the average value as the turbidity value. The greater the turbidity, the lower the transparency. >1000NTU means that it exceeds the measurement range of the instrument or the detector signal is too low.

[0154] Table 8: Product appearance and turbidity test results

[0155]

[0156] Conclusion: A composite composition containing an alcohol-soluble or oil-soluble active ingredient and chitosan was prepared to examine the composite effect of the active ingredient and chitosan, as well as the effect on the transparency of the system. According to the product appearance scoring and turbidity results in the above table, the composite compositions prepared in Examples 18 to 20 were all opaque.

Claims

1. A composition comprising chitosan and ferulic acid, wherein: The weight ratio of chitosan to ferulic acid is 0.7-0.8:1, and the pH of the composition is 2-7.

2. The composition according to claim 1, characterized in that The composition also comprises ethanol or a polyol.

3. The composition according to claim 2, characterized in that The polyol is selected from propylene glycol, butylene glycol, glycerol, hexylene glycol, or a combination thereof.

4. The composition according to claim 1, characterized in that The content of ferulic acid in the composition is 0.1-3% by weight, and the content of chitosan is 0.1-3% by weight.

5. The composition according to claim 2, characterized in that The amount of ethanol or polyol in the composition is 5-30% by weight.

6. A method for preparing the composition according to claim 1, comprising the steps of: a) dissolving chitosan with ethanol or polyol; b) adding chitosan according to the weight ratio of chitosan to ferulic acid of 0.7-0.8:1, stirring until dissolved, c) adding water to obtain a composition comprising chitosan and ferulic acid.

7. The method according to claim 6, characterized in that The polyol is selected from propylene glycol, butylene glycol, glycerol, hexylene glycol, or a combination thereof.

8. Use of the composition as claimed in claim 1 in cosmetics.

9. The use according to claim 8, characterized in that The cosmetic is a water-based cosmetic.

10. The cosmetic according to claim 8, characterized in that The cosmetic further comprises auxiliary materials acceptable in the cosmetics field.